PERANCANGAN SISTEM WEB-BASE STUDENT PROFILING UNTUK PENENTUAN JURUSAN DI MA NURUL KHOIROH - Eka Rahmawati; Irma Yunita; Novia Rofiatul Chasanah (CV. Denasya Smart Publisher, 2025)
The selection of study majors in secondary schools is often conducted manually and subjectively, which may lead to inappropriate student placement. This study designs a web-based information system for student profiling to determine majors at MA Nurul Khoiroh. The system was developed using the Waterfall model, including requirements analysis, system design with a Context Diagram, Data Flow Diagram (DFD), Entity Relationship Diagram (ERD), and user interface design. The system is designed to allow students to log in, complete an interest test, and automatically receive major recommendations, while administrators can manage student data, test questions, and test results. The design results show that the system can provide objective recommendations and facilitate academic data management. This research contributes to improving the efficiency, accuracy, and objectivity of the major selection process, although the actual implementation is still limited to the design stage.